St. Kitts and Nevis : Fourth Review Under the Stand-By Arrangement, Financing Assurances Review and Request for Waivers of Applicability-Staff Report and Press Release. (IMF Staff Country Reports; Country Report, 2013)
Economic activity continued to shrink in St. Kitts and Nevis in 2012 on account of a sharp slowdown in the construction sector. Despite the sluggish global environment, the authorities have continued to successfully implement their economic program. Inflation has stabilized. The external position is relatively stable since the improved trade balance. Bank credit is restrained by the sluggish economy and rising nonperforming loans (NPLs). Despite the continued economic contraction, all of the fiscal targets are met owing to strong non-tax and income tax receipts.